(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
As a result of modern lifestyle changes, workplace stress, and pollution from the environment, men’s lives no longer attain balance between body, mind, and spirit. Ayurveda has been assigned a rescue function in this situation to restore those lives through a tranquil healthcare system. Ayurveda, which dates back more than a thousand years, has established a legacy in the region known as India, with Kerala, a South’ Indian state, contribution a diversity of therapies and techniques to cure different aches, pains, and chronic disease. Because of this, residents of neighboring states and foreign visitors are travelling to Kerala in order to have a full-body cure. The results showed that the opinion of Indian healthcare customers is different from that of immigrants with respect to marriage and education generally under both constructs of quality of service and patient satisfaction, then age and gender groups particularly for the same constructs, accordingly the independent sample t-test and Analysis of variation were the methods of statistical analysis used. The study is timely since it includes an empirical suggestion to the management to help them comprehend how different persons are thinking about and perceiving their services, and which aspects will need more attention when it comes time to improve the Ayurveda health care system.